Dynamic behavior of pile-supported wharves by slope failure during earthquake via centrifuge tests - Jung-Won Yun; Jin-Tae Han (International Journal of Geo-Engineering, 2021)
Abstract The effects of earthquakes on pile-supported wharves include damage to piles by inertial forces acting on the superstructure, and damage caused by horizontal displacement of retaining walls. Piles can also be damaged through kinematic forces generated by slope failure. Such forces are significant but it is difficult to clearly explain pile damage during slope failure since the inertial force of superstructure and the kinematic force by slope failure can occur simultaneously during an earthquake. In this study, dynamic centrifuge model tests were performed to evaluate the effect of the kinematic force of the ground due to slope failure during earthquake on the behavior of a pile-supported wharf structure. Experimental results indicate that the slope failure in the inclined-ground model caused the deck plate acceleration and pile moment to be up to 24% and 31% respectively greater than those in the horizontal-ground model due to the kinematic force of the ground.